Reaksi Pasar Saham di Indonesia terhadap Keterbukaan Informasi Terkait Transaksi Afiliasi - Olivia Sirait; Arief Wibisono Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Affiliated transaction or also known as related party transaction (RPT) refers to a transaction involving two or more parties with a special or related relationship. Due to this relationship, the transactions may not be conducted according to the arm's length principle or cause a potential agency problem. Therefore, information disclosure to the public is necessary to provide a material information regarding affiliated transactions and as a key aspect of adhering to principles of good corporate governance. The aim of this study is to analyze whether there is a significant and positive impact on Indonesian stock market, in response to the RPT Announcements by issuers in Indonesia. Despite the prevalence of affiliated transactions among group companies in Indonesia, there is little research focused on the impact of RPT announcements on stock market reactions in Indonesia. Using event study as the method, in this study assess whether stock prices adjust in a timely manner upon the arrival of new public information. The results indicate that there is a significant and positive average abnormal return on the third trading day before RPT Announcement, and a significant and negative average abnormal return on the fourth trading day after RPT Announcement. Keywords: Stock market reaction, RPT announcement, affiliated transaction, event study